Severe Immediate and Delayed Hypersensitivity Reactions to Biologics in a Toddler With Systemic Juvenile Idiopathic Arthritis. (February 2022) - Villacis-Nunez, D. Sofia; Bilcha, Kassahun; Spraker, Mary; Rouster-Stevens, Kelly; Cooley, Anthony
Many pediatric rheumatic diseases can be safely managed with biologic therapy. Severe allergic reactions to these medications are uncommon. We report the case of a 2-year-old male with systemic-onset juvenile idiopathic arthritis and secondary macrophage activation syndrome (MAS), whose treatment was complicated by severe allergic reactions to biologics, including drug reaction with eosinophilia and systemic symptoms (DRESS)/drug-induced hypersensitivity reaction (DIHR) likely due to anakinra, and anaphylactoid reaction to intravenous tocilizumab. These required transition to canakinumab, cyclosporine, and corticosteroids, with later development of interstitial lung disease and MAS flare needing transition from canakinumab to tofacitinib, which led to disease control. Whether lung disease is a manifestation of DRESS/DIHR to canakinumab remains unclear. High index of suspicion of hypersensitivity reactions for timely diagnosis and drug discontinuation is critical, especially in patients with active disease who might be at increased risk of these adverse events.